Laser Balloon or Wide-Area Circumferential Irrigated Radiofrequency Ablation for Persistent Atrial Fibrillation: A Multicenter Prospective Randomized Study. (December 2017) - Schmidt, Boris; Neuzil, Petr; Luik, Armin; Osca Asensi, Joaquin; Schrickel, Jan Wilko; Deneke, Thomas; Bordignon, Stefano; Petru, Jan; Merkel, Matthias; Sediva, Lucie; Klostermann, Annemarie; Perrotta, Laura; et al.
Abstract : Background: Pulmonary vein isolation is the cornerstone of ablation for persistent atrial fibrillation (AF). The role of balloon catheters in this patient population remains ill defined. We sought to compare efficacy and safety of the laser balloon (LB) with wide-area circumferential pulmonary vein isolation using irrigated radiofrequency current (RF) ablation and 3-dimensional mapping. Methods and Results: In 6 European centers, patients with persistent AF were prospectively randomized. Follow-up included 3-day Holter ECG recordings and office visits at 3, 6, and 12 months. The primary efficacy end point was freedom from AF between 90 and 365 days after a single ablation. The primary safety end point was the incidence of any periprocedural complications. Of 152 enrolled patients, 134 (n=68 LB and 66 RF; 63% men; mean age, 66+10 years) with persistent AF (median AF history, 14 months; Q1–Q3, 7–36 months) underwent pulmonary vein isolation and completed the entire follow-up. Baseline parameters were similar in both groups. Procedure and fluoroscopy times were similar in both groups (135±38 and 14±9 minutes (LB) versus 128±51 and 11±9 minutes). The primary efficacy end point was met by 71.2% versus 69.3%, in the LB and RF groups, respectively ( P =0.40). In the LB group, stroke (n=1), a false aneurysm (n=1), and phrenic nerve palsy (n=1) were observed. In the RF group, 2 patients developed a false aneurysm, and 1 patient needed surgical repair. Conclusions: An LB-guided strategy was associated with similar efficacy as wide-area circumferential pulmonary vein isolation using irrigated RF in patients with persistent AF. Clinical Trial Registration: https://www.clinicaltrials.org . Unique identifier: NCT01863472.